2017
DOI: 10.1080/15376516.2016.1273422
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Asiatic acid attenuates pre-neoplastic lesions, oxidative stress, biotransforming enzymes and histopathological alterations in 1,2-dimethylhydrazine-induced experimental rat colon carcinogenesis

Abstract: Asiatic acid (AA), a pentacyclic triterpenoid, derived from the tropical medicinal plant Centella asiatica is known to exhibit numerous pharmacological properties. We hypothesized that AA will have chemopreventive potential against 1,2-dimethylhydrazine (DMH)-induced experimental colon carcinogenesis in male Wistar rats. Rats were arbitrarily divided into six groups. Group I rats were processed as control. Group II rats received AA (8 mg/kg b.w., p.o.) and groups III-VI rats received subcutaneous injections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…It also has a certain therapeutic effect on gastrointestinal tumors. Three mechanisms are reported in the studies: asiatic acid can reduce the level of pro-apoptotic factors (B-cell lymphoma 2(Bcl-2) ↑, Bcl-2-associated X protein(Bax) ↓, caspase-3 ↓), and related inflammation factors (TGF-β1 ↓, TNF-α ↓, IL-6 ↓, IL-1β ↓), and increase the level of anti-oxidative stress factors (SOD ↑, GSH-Px ↑, CAT ↑, GST ↑, GSH ↑) ( Xiao et al, 2017 ; Siddique et al, 2017 ; Wei et al, 2018 .). The study on madecassoside found that it could ameliorate drug-induced acute liver failure by reducing inflammation (TNF-α ↓, IL-1β ↓, IL-6 ↓, iNOS ↓, COX-2 ↓) and oxidative stress (SOD ↑, CAT ↑, GPx ↑, Nrf2 ↑, HO-1 ↑) ( Wang W. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…It also has a certain therapeutic effect on gastrointestinal tumors. Three mechanisms are reported in the studies: asiatic acid can reduce the level of pro-apoptotic factors (B-cell lymphoma 2(Bcl-2) ↑, Bcl-2-associated X protein(Bax) ↓, caspase-3 ↓), and related inflammation factors (TGF-β1 ↓, TNF-α ↓, IL-6 ↓, IL-1β ↓), and increase the level of anti-oxidative stress factors (SOD ↑, GSH-Px ↑, CAT ↑, GST ↑, GSH ↑) ( Xiao et al, 2017 ; Siddique et al, 2017 ; Wei et al, 2018 .). The study on madecassoside found that it could ameliorate drug-induced acute liver failure by reducing inflammation (TNF-α ↓, IL-1β ↓, IL-6 ↓, iNOS ↓, COX-2 ↓) and oxidative stress (SOD ↑, CAT ↑, GPx ↑, Nrf2 ↑, HO-1 ↑) ( Wang W. et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…DMH was dissolved in1mM EDTA just ahead of use and the pH adjusted to 6.5 with 1 mM NaOH to make sure the stability of carcinogen. Animals were given subcutaneous injections of DMH at a dose of 20 mg/kg body weight for 4 consecutive weeks of the total experimental period [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…AA reduced polyps and aberrant crypt foci and salvaged colonic tissues following reduction in lipid peroxidation and restoration of antioxidant defense in the colon. In another study, the protective mechanism in colon cancer was demonstrated by virtue of anti-inflammatory, antiproliferative, and pro-apoptotic properties of AA (Siddique et al, 2017 ). AA improved disease activity indices, decreased phase I metabolic enzymes and improved phase II metabolic enzymes and mucin in colon cancer in rats induced by DMH.…”
Section: Asiatic Acid In Colon Cancermentioning
confidence: 99%